'Race', youth sport, physical activity and health : global perspectives - Dagkas, Symeon; Azzarito, Laura; Hylton, Kevin, 1964- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"'Race', Youth Sport, Physical Activity and Health provides a resource that addresses 'race' and racism in an accessible way by contextualizing theory with practical evidence-based examples drawn from global geographical and cultural settings. This is the first book to focus on issues of 'race' and racism in youth sport, physical activity and health. Drawing on critical race theory, intersectionality and post-feminism, and presenting a range of international empirical case studies, it explores racialization processes in pedagogical and non-pedagogical settings. The book examines how 'race' and racism in pedagogical settings shape young peoples' dispositions towards participation in sport and physical activity, and how identity discourses are being shaped in contemporary sport, physical activity and health. Essential reading for anybody working in sport and exercise studies, physical education, sociology or health studies"--
Introduction -- the project -- Race, racism and race logic -- Social justice and intersectionality in sport, physical activity and health pedagogy: creating connections -- Why is our PE teacher education curriculum white? a collaborative self-study of teaching about race in PETE programmes -- Stories of difference and sameness: South Asian, Muslim young women talk physical education, -- Athleticising young black lives: confusing education with commerce in high school sports -- "Playing the game" and "finding my way": minority ethnic female PE teachers' counter-stories -- Race logic in American college sports: athletic exploitation, privilege and institutional resentment -- Challenging the stereotypical construction of black physical superiority and intellectual inferiority in sport -- Le parkour, freerunning and young white men: identities, resistances and digital representations -- Sport and the normalisation of Australian aboriginal peoples -- British Asians, racial framing and football exclusion -- Physicality and health inequalities in British Pakistani Muslim women: analysis of a participatory theatre-based play -- Decolonising health in education: considering Indigenous knowledge in policy documents -- The "health gap" from a social justice perspective: critical race theory, post colonialism, and post-feminism.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Racism in sports -- Case studies; Discrimination in sports -- Case studies; Sports for children -- Social aspects -- Case studies; Exercise -- Social aspects -- Case studies; Equality -- Health aspects -- Case studies; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; EDUCATION / Physical Education; HEALTH & FITNESS / Exercise